Aβ Deposits in the Neocortex of Adult and Infant Hypoxic Brains, Including in Cases of COVID-19. Issue 12 (20th October 2022) - Priemer, David S; Rhodes, Charles Harker; Karlovich, Esma; Perl, Daniel P; Goldman, James E
Abstract: The brain of a 58-year-old woman was included as a civilian control in an ongoing autopsy study of military traumatic brain injury (TBI). The woman died due to a polysubstance drug overdose, with Coronavirus Disease 2019 (COVID-19) serving as a contributing factor. Immunohistochemical stains for β-amyloid (Aβ), routinely performed for the TBI study, revealed numerous, unusual neocortical Aβ deposits. We investigated the autopsied brains of 10 additional young patients (<60 years old) who died of COVID-19, and found similar Aβ deposits in all, using two different Aβ antibodies across three different medical centers. The deposits failed to stain with Thioflavin-S. To investigate whether or not these deposits formed uniquely to COVID-19, we applied Aβ immunostains to the autopsied brains of COVID-19-negative adults who died with acute respiratory distress syndrome and infants with severe cardiac anomalies, and also biopsy samples from patients with subacute cerebral infarcts. Cortical Aβ deposits were also found in these cases, suggesting a link to hypoxia. The fate of these deposits and their effects on function are unknown, but it is possible that they contribute to the neurocognitive sequelae observed in some COVID-19 patients. Our findings may also have broader implications concerning hypoxia and its role in Aβ deposition in the brain.